The key risks of interaction between employment services and employers in the labor market and the ways of their localization - V. Vinogradova, Marina (2020)
The article discusses the risks in the process of interaction between employment services and the employer in the regional labor market. Risks become barriers to the implementation of employment policy and the formation of effective mechanisms for the development of labor resources. The main problems and contradictions are associated with the creation of legal, economic, institutional and informational conditions. The creation of conditions will contribute to the effective functioning of the labor market, which will bridge the gaps between supply and demand for labor. The main problems can be distinguished by the method of questionnaire sociological survey and in-depth informal interview. Such a survey is conducted based on a representative sample from all over Russia. Based on analysis of the survey results highlighted the main risks of interaction in the labor market, a description and evaluations and the level of risk, risk sharing on the subjects of relations, possible areas of risk containment and mitigation of their consequences. The main conclusion of the work is the provision on the need to form an integrated risk management system. The integrated system will ensure the main directions of stable development of the regional labor market.